A Two-Step Matrix-Free Secant Method for Solving Large-Scale Systems of Nonlinear Equations - M. Y. Waziri; W. J. Leong; M. Mamat (Journal of Applied Mathematics)
We propose an approach to enhance the performance of a diagonal variant of secant method for solving large-scale systems of nonlinear equations. In this approach, we consider diagonal secant method using data from two preceding steps rather than a single step derived using weak secant equation to improve the updated approximate Jacobian in diagonal form. The numerical results verify that the proposed approach is a clear enhancement in numerical performance.